Disaggregated Energy Consumption and Sectoral Outputs in Thailand: ARDL Bound Testing Approach - Nathan, Thurai Murugan; Liew, Venus Khim-Sen; Wong, Wing-Keung (Geist Science, 2016)
From an economic perspective, energy-output relationship studies have become in-creasingly popular in recent times, partly fuelled by a need to understand the effect of energy on production outputs rather than overall GDP. This study dealt with disaggregated energy consump-tion and output of some major economic sectors in Thailand. ARDL Bound Testing approach was employed to examine the co-integration relationship. The Granger causality test of the afore- mentioned ARDL framework was done to investigate the corresponding causality effect. Results showed that, from year 1980 to 2010, productivity of most scrutinized industries was highly reliant on crude oil and natural gas. However, coal usage in transportation and agricultural industries can be reduced without affecting productivity. Few recommendations are given thereafter for Thailand to better manage their imported and local energy sources.